Abenaki materials, Floyd G. Lounsbury Papers - Lounsbury, Floyd Glenn; Day, Gordon M. (1956)
The Abenaki materials in the Lounsbury Papers includes corresondence from Gordon Day on the eastern border between the Iroquois and Abenaki in Series I. A recording on Abenaki kinship terms can be found in Series VII.